Enhancing Students’ Self-Regulated Learning Abilities and Academic Achievement in Chemistry Education: A Quantitative Assessment of Information and Communication Technology-Assisted Instructional Model - Udu, David Agwu; Mbamalu, Oby Justina (Journal of chemical education, 2025)
Chemistry is an essential subject for most science-based undergraduate courses in universities; as such, it is a basic requirement for secondary school students aspiring to study science-related courses in universities. However, the subject has historically been linked to high failure rates and underperformance of students in secondary school standardized local and national examinations in most developing nations, like Nigeria. This trend may stem from the students’ perceived low self-regulation in learning. In this study, one of the active learning pedagogies, specifically, the information and communication technology-assisted instructional model (ICTAIM), was evaluated on learners in secondary schools to determine its effect on self-regulation and achievement in chemistry. Results showed a statistically significant improvement in both areas, with a moderate positive linear correlation between achievement and self-regulation among the learners. The findings suggest that employing active learning strategies like ICTAIM, which promote student engagement, can enhance chemistry understanding and skills. Additionally, the study advocates for the adoption of collaborative and participatory teaching methods, emphasizing the importance of training teachers in these pedagogies to improve chemistry education in developing nations.